Characterization of walleye dermal sarcoma virus Orf B during tumor development - Daniels, Candelaria Christina, author; Quackenbush, Sandra L., advisor (Colorado State University. Libraries, 2008)
Walleye dermal sarcoma virus is a complex retrovirus associated with walleye dermal sarcomas (WDS). These sarcomas develop and regress on a seasonal basis, providing a unique model to study mechanisms of tumor development and regression in vertebrates. WDS is experimentally transmissible to walleye with cell-free, regressing tumor homogenates. During the fall, low levels of spliced accessory gene transcripts, A and B, are present in developing tumors suggesting that their encoded proteins, rv-cyclin and Orf B, may play a role in oncogenesis. Infectious virus and high levels of full-length viral RNA and spliced accessory and env transcripts are expressed during tumor regression, the following spring. The three accessory proteins Orf A (rv-cyclin), Orf B, and Orf C function in tumor development and regression. In explanted tumor and mammalian cells stably expressing the 35kDa Orf B protein, Orf B is localized at the cell periphery in structures similar to focal adhesions and along actin stress fibers. Results from these studies demonstrate Orf B interacts directly or in a complex with several cellular proteins important in signal transduction pathways: receptor for activated C kinase (RACK1), protein kinase C alpha (PKCα), Src, phosphatidylinositol-3-kinase (PI3K), and protein phosphatase 2A (PP2A). The cellular proteins BAD, 90kDa ribosomal S6 kinase (p90RSK), PKCα, and protein kinase B (AKT), which are important in controlling apoptosis and/or proliferation, are activated in Orf B-expressing cells. Orf B protects cells from staurosporine-induced apoptosis and induces cell proliferation of Orf B-expressing cells under serum-deprived conditions suggesting a mechanism of action for tumor development. Expression of Orf B induces transformation of NIH3T3 cells in vitro and a PI3K and mTOR inhibitor prevented transformation, providing the first evidence that Orf B induces a transformed phenotype. The regulation of cell signaling pathways is one way in which viruses induce oncogenesis. Orf B ensures the establishment of dermal sarcoma by activating signal transduction pathways that control cell survival and proliferation such as PKC and Akt.
Keywords: oncogenesis; Orf b; protein kinase C; RACK1; retroviruses; signal transduction; WDSV; walleye dermal sarcoma virus; microbiology; virology